Platelet and neutrophil responses to Porphyromonas gingivalis in human whole blood. (20th April 2021) - Chen, William A.; Fletcher, Hansel M.; Payne, Kimberly J.; Aka, Sheryl; Thornburg, Melanie B.; Gheorghe, Joseph D.; Safi, Shahnaj Binte; Shavlik, David; Oyoyo, Udochukwu; Boskovic, Danilo S.
Abstract : Porphyromonas gingivalis is a causative agent for periodontal disease. Binding of platelets to this gram‐negative anaerobe can regulate host hemostatic (thrombus forming) and immune (neutrophil interacting) responses during bacterial infection. Additionally, in response to bacterial pathogens neutrophils can release their DNA, forming highly prothrombotic neutrophil extracellular traps (NETs), which then further enhance platelet responses. This study evaluates the role of P . gingivalis on platelet expression of CD62P, platelet–neutrophil interactions, and labeled neutrophil‐associated DNA. Human whole blood was preincubated with varying P . gingivalis concentrations, with or without subsequent addition of adenosine diphosphate (ADP). Flow cytometry was employed to measure platelet expression of CD62P using PerCP‐anti‐CD61 and PE‐anti‐CD62P, platelet–neutrophil interactions using PerCP‐anti‐CD61 and FITC‐anti‐CD16, and the release of neutrophil DNA using FITC‐anti‐CD16 and Sytox Blue labeling. Preincubation with a high (6.25 × 10 6  CFU/mL) level of P . gingivalis significantly increased platelet expression of CD62P in ADP treated and untreated whole blood. In addition, platelet–neutrophil interactions were significantly increased after ADP stimulation, following 5–22 min preincubation of blood with high P . gingivalis CFU. However, in the absence of added ADP, platelet–neutrophil interactions increased in a manner dependent on the preincubation time with P . gingivalis . Moreover, after ADP addition, 16 min preincubation of whole blood with P . gingivalis led to increased labeling of neutrophil‐associated DNA. Taken together, the results suggest that the presence of P . gingivalis alters platelet and neutrophil responses to increase platelet activation, platelet interactions with neutrophils, and the level of neutrophil antimicrobial NETs.